Spatial patterns and drivers of soil total nitrogen in anthropogenic shrub encroachment in desert steppe - Zhao, Yanan; Li, Zhili; Cao, Zhe; Mi, Wenbao; Wang, Hongmei (Frontiers in Environmental Science, 2023)
Nitrogen is the most important driving factor in primary production and decomposition in arid and semi-arid ecosystems. The effects of shrub encroachment on nitrogen cycling have been investigated at the site scale but seldomly conducted at the landscape scale. Here, we selected 43 shrubland sites distributing across 3000 km2 area in temperate desert grassland in eastern Yanchi County of Ningxia Hui Autonomous. We investigated the spatial heterogeneity and driving factors of soil total nitrogen (STN) at the landscape scale by using geostatistical analysis and the geographical detector method. Our results showed that the average STN decreased in the order of 0 - 5 cm (0.21 g·kg-1) > 5 - 15 cm (0.19 g·kg-1) > 15 - 40 cm (0.18 g·kg-1). Geostatistical analysis showed that STN exhibited the strong spatial autocorrelation in the 0 - 5 and 5 - 15 cm soil layers and the moderate spatial autocorrelation in the 15 - 40 cm soil layer. Furthermore, the geographic detector method indicated that soil physicochemical properties exhibited the stronger effects than these of topographic and vegetation biomass in determining the spatial distribution of STN. Specifically, soil water content in the 0 - 20 cm soil layer explained 35% of variation in STN spatial pattern in the 0 - 5 cm soil layer, while soil organic carbon content in the 15 - 40 cm soil layer explained 64% and 45% of variation in STN spatial patterns in the 5 - 15 cm and 15 - 40 cm soil layers, respectively. It was concluded that soil water content and organic carbon content primarily drove the formation of STN spatial heterogeneity in shrubland at the landscape scale, indicating that anthropogenic shrub encroachment evidently affected soil water content and redistribution in dryland.